The Powder of Sympathy - Morley, Christopher, 1890-1957; Duncan, Walter Jack, 1881-1941 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Powder of Sympathy" by Christopher Morley is a collection of essays reflecting on various aspects of life and journalism, written in the early 20th century. The work serves as a platform for the author to articulate his thoughts on humanity, culture, and the arts$1 (Boften with wit and a touch of nostalgia. The essays are likely inspired by Morley$1 (Bs experiences as a journalist, offering insights blended with humor and philosophical musings. At the start of the book, the author sets the tone by addressing his friends in a heartfelt dedication, claiming that the essays often originated from the lively chaos of his mind. He mentions the ephemeral nature of his writings, which have been compiled from newspaper columns, and expresses the hope that they might inspire future generations of journalists. Morley discusses the candid nature of columnists, who often share their unfiltered opinions and observations, and reflects on the rich interplay between critics, the arts, and the world around them. Through this opening portion, readers are invited into Morley's thoughtful, often humorous exploration of life's fleeting moments, as he seeks to capture its essence in writing. (This is an automatically generated summary.)s
An Oxford symbol -- Scapegoats -- To a New Yorker a hundred years hence -- A call for the author -- Mr. Pepys's Christmases -- Children as copy -- Hail, kinsprit! -- Round Manhattan Island -- The unknown citizen -- Sir Kenelm Digby -- First impressions of an amiable visitor -- In honorem: Martha Washington -- According to Hoyle -- L. E. W. -- Our extension course -- Some recipes -- Adventures of a curricular engineer -- Santayana in the subway -- Madonna of the taxis -- Matthew Arnold and exodontia -- Dame Quickly and the Boilroaster -- Vacationing with De Quincey -- The Spanish Sultry -- What kind of a dog? -- A letter from Gissing -- July 8, 1822 -- Midsummer in Salamis -- The story of Ginger Cubes -- The editor at the ball game -- The Dame explores Westchester -- The power and the glory -- Gissing joins a country club -- Three stars on the back stoop -- A Christmas card -- Symbols and paradoxes -- The return to town -- Maxims and minims -- Two reviews -- Buddha on the L -- Intellectuals and roughnecks -- The fun of writing -- A Christmas soliloquy.
Release date is 2022-01-17
Emmanuel Ackerman, Charlie Howard, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: American essays -- 20th century